THE CARPET PARADIGM AND THE BLUE TILE FROM THE WALL OF DAMASCUS, THE GRID AND THE ARABESQUE - Cojanu, Cristina (European Scientific Journal, ESJ, 2014)
That painting is understood as being visual cannot really be contested. Even when Duchamp introduced his disavowal of painting and the schema of the chessboard to indicate an anti-retinal strategy, the implication of visual imaginary was still in place. Indeed the link between knowing and seeing is not only at the root of metaphysical (the desire to know is the desire to see —Aristotle) thinking itself, but persists even within the disavowal of it within Late Modernity. This paper takes two key concepts from the discourse of painting in Late Modernity, the carpet paradigm and the grid, and looks at them through the idea of the arabesque and the ornamental. The arabesque is not a schema of a visual revelation, but the perceptive, as-wellas intermediary of donation and reception of form in re-presentation and the ornamental does not realise itself as ornament, even though it is also a form of manifested (planar) surfaceembellishment, a tensely contracted figure-ground collapse. The ornamental is here the activity of form itself, the plasticity of beings, the ―becoming essential of accident‖ and, at the same time, ―the becoming accidental of essence‖, as the capacity to receive and to produce form simultaneously. Meaning as a constant emergence of meaning, infinitely deferring from ‗taking‘.